THE MEANING AND CHARACTERISTICS OF PUBLIC POLICY IN INTERNATIONAL ARBITRATION - Asal Juraeva (Journals Park Publishing, 2024)
Public policy (PP) doctrine, being a substantial concept in many jurisdictions, is also among the evasive concepts given the contrary to practical application in the case law and complicated literature that is argued before many judges at different multinational levels. As a notion, PP has a vital impact on the execution of ICA awards in many adaptable ways.
Keywords: arbitration; international commerce; public policy.